2008
DOI: 10.1007/s00125-008-1085-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of the peri-islet basement membrane in NOD mice: a barrier against destructive insulitis

Abstract: Aims/hypothesis This study examined whether the capsule which encases islets of Langerhans in the NOD mouse pancreas represents a specialised extracellular matrix (ECM) or basement membrane that protects islets from autoimmune attack. Methods Immunofluorescence microscopy using a panel of antibodies to collagens type IV, laminins, nidogens and perlecan was performed to localise matrix components in NOD mouse pancreas before diabetes onset, at onset of diabetes and after clinical diabetes was established (2-8.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 32 publications
5
110
1
Order By: Relevance
“…It has earlier been shown that LM-411 and LM-511 are the major LM isoforms in vascular basement membranes [29]. In addition, the peri-islet capsule seems to be composed of LM chains α2, β1 and γ1, suggesting the presence of LM-211 [30]. At least in humans, LM-421 and LM-521 also seem to be present in the islet basement membranes [31].…”
Section: Discussionmentioning
confidence: 95%
“…It has earlier been shown that LM-411 and LM-511 are the major LM isoforms in vascular basement membranes [29]. In addition, the peri-islet capsule seems to be composed of LM chains α2, β1 and γ1, suggesting the presence of LM-211 [30]. At least in humans, LM-421 and LM-521 also seem to be present in the islet basement membranes [31].…”
Section: Discussionmentioning
confidence: 95%
“…Further, lysolipids and eicosanoids act as "chemoattractants" ( 230,(279)(280)(281), and increased generation of these could promote migration of immune cells toward the islet and subsequent infi ltration, raising the possibility that in vivo inhibition of iPLA 2 ␤ could mitigate immune responses leading to T1D. Autoimmune insulitis is marked by degradation of the islet basement membrane, which presents a physical barrier to infi ltrating leukocytes ( 282 ). Remarkably, the abundance of infi ltrating cells is signifi cantly reduced in NOD mice treated with FKGK18 ( 161 ).…”
Section: Ipla 2 ␤ and Diseasesmentioning
confidence: 99%
“…Conversely, the extent to which islets and β cells use intrinsic defense and survival mechanisms for their protection has largely been underexplored. We recently reported that in situ NOD mouse islets are surrounded by a continuous basement membrane (BM) containing the heparan sulfate proteoglycan (HSPG) perlecan (19). HSPGs consist of a core protein to which a number of side-chains of the glycosaminoglycan or complex sugar heparan sulfate (HS) are covalently attached.…”
Section: Introductionmentioning
confidence: 99%